2020
DOI: 10.1111/ejh.13517
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on relapse in children with acute lymphoblastic leukemia treated according to Nordic treatment protocols

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…In our previous study, we concluded that obesity at diagnosis was associated independently with the risk of relapse in older children with ALL 4 . We hypothesised that obese older children experience more severe toxic events than healthy‐weight children and therefore their treatment may have been modified, contributing to the increased risk of relapse.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our previous study, we concluded that obesity at diagnosis was associated independently with the risk of relapse in older children with ALL 4 . We hypothesised that obese older children experience more severe toxic events than healthy‐weight children and therefore their treatment may have been modified, contributing to the increased risk of relapse.…”
Section: Introductionmentioning
confidence: 98%
“…20 In our previous study, we concluded that obesity at diagnosis was associated independently with the risk of relapse in older children with ALL. 4 We hypothesised that obese older children experience more severe toxic events than healthyweight children and therefore their treatment may have been modified, contributing to the increased risk of relapse. To explore the underlying factors behind the higher relapse risk and inferior outcomes in this patient group, we studied the role of obesity in the occurrence of severe adverse events and treatment delays in children with ALL treated according to the non-high-risk arm of the NOPHO ALL2008 study.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity increases the incidence and mortality of many cancers (13)(14)(15), including leukemia. In children with acute lymphoblastic leukemia (ALL), obesity increases relapse rate by ~50% (16,17) and risk of detectible minimal residual disease after the first month of chemotherapy more than two-fold (18). Tucci et al uncover a previously unidentified interaction between ALL cells and adipocytes, leading to transfer of free fatty acids for use as a metabolic fuel and macromolecule building block.…”
Section: Editorial On the Research Topic Metabolic Rewiring In Leukemiasmentioning
confidence: 99%
“…However, they have been poorly addressed by nutritional intervention during pediatric cancer therapy. A high BMI and obesity at diagnosis is another form of malnutrition associated with an increased risk of complications (i.e., wound infection and arterial thrombosis) [ 24 ] and, in acute lymphoblastic leukemia (ALL), of disease relapse [ 25 ].…”
Section: Introductionmentioning
confidence: 99%